2015
DOI: 10.1002/adma.201505008
|View full text |Cite
|
Sign up to set email alerts
|

Solution‐Processable Glass LiI‐Li4SnS4 Superionic Conductors for All‐Solid‐State Li‐Ion Batteries

Abstract: A new, highly conductive (4.1 × 10(-4) S cm(-1) at 30 °C), highly deformable, and dry-air-stable glass 0.4LiI-0.6Li4 SnS4 is prepared using a homogeneous methanol solution. The solution process enables the wetting of any exposed surface of the active materials with highly conductive solidified electrolytes (0.4LiI-0.6Li4 SnS4), resulting in considerable improvements in the electrochemical performance of these electrodes over conventional mixture electrodes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
261
1

Year Published

2017
2017
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 279 publications
(273 citation statements)
references
References 49 publications
11
261
1
Order By: Relevance
“…2 is encouraging. It is interesting to note that two other groups 6,7 have recently reported preparations of Li 4 SnS 4 using relatively low temperature processing similar to that of Kaib, Haddadpour, et al 3 Both of these studies report X-ray diffrac- tion patterns, presumably measured at room temperature, which show strong similarity to the patterns for Li 4 SnS * 4 shown in Fig. 2.…”
Section: Simulated Crystal Structuressupporting
confidence: 56%
See 1 more Smart Citation
“…2 is encouraging. It is interesting to note that two other groups 6,7 have recently reported preparations of Li 4 SnS 4 using relatively low temperature processing similar to that of Kaib, Haddadpour, et al 3 Both of these studies report X-ray diffrac- tion patterns, presumably measured at room temperature, which show strong similarity to the patterns for Li 4 SnS * 4 shown in Fig. 2.…”
Section: Simulated Crystal Structuressupporting
confidence: 56%
“…Sahu et al 6 showed that Li 4 SnS 4 and its alloys with Li 3 AsS 4 have reasonable ionic conductivity (10 −5 -10 −4 S/cm at room temperature) with comparatively more air-stability than other sulfide electrolytes. Park et al 7 demonstrated favorable conductivity and stability properties of Li 4 SnS 4 and its alloys with LiI.…”
mentioning
confidence: 99%
“…This gives us a hint that to improve the electrochemical performance of lithium argyrodite-based all-solid-state batteries fabrication of better interfacial contacts is essential. 3436 …”
Section: Resultsmentioning
confidence: 99%
“…In the preparation of Li PS Cl through the solution process, ethanol was used for the solvent [ 6 ]. Other solvents used to prepare solid electrolyte solutions are anhydrous hydrazine [ 7 ] (Li Ge P S , σ = 1.82 × 10 S/cm), tetrahydrofuran [ 8 ] (β Li PS , σ = 1.6 × 10 S/cm), acetonitrile [ 9 ] (Li P S I, σ = 6.3 × 10 S/cm), methylformamide [ 10 ] (Li PS , σ = 2.6 × 10 S/cm), methanol [ 11 ] (LiI Li SnS , σ = 4.1 × 10 S/cm), and ethanol [ 6 ] (Li PS Cl, σ = 1.4 × 10 S/cm). Solvents such as methanol or ethanol are more attractive to scalable procedures since they have low boiling points that allow the composite cathode to be obtained easily.…”
Section: Introductionmentioning
confidence: 99%